Clinical Features and Prognosis in Chinese Patients With Dipeptidyl–Peptidase–Like Protein 6 Antibody–Associated Encephalitis - Miao, Ailiang; Shi, Yongwei; Wang, Xiaoshan; Ge, Jianqing; Yu, Chuanyong (Frontiers in Neurology, 2022)
Objectives: Anti-dipeptidyl–peptidase–like protein 6 (anti-DPPX) encephalitisis an extremely rare type of immune-mediated encephalitis. This study aimed to analyze the electroclinical characteristics and prognosis of anti-DPPX encephalitis. Methods: 5 patients ( all male) with anti-DPPX encephalitis in East China from January 2016 to October 2021 was retrospective analyzed. Electroclinical features and outcomes were reviewed. Results: All five patients were male. The media age at disease onset was 32 years old with a range of 14-56 years. The main symptoms included psychiatric disturbances (2/5), amnesia (4/5), confusion (3/5), and seizures (3/5). Migrating myoclonus were identified in patient 4 with positive DPPX and contactin-associated protein-like 2 antibody in blood. All of the patients had positive DPPX antibodies in serum. Only one of them had positive antibody in the cerebrospinal fluid. EEG showed diffuse slowing in two patients, but no epileptiform discharges were observed. 80% (4/5) of the patients showed normal brain magnetic resonance imaging. After immunotherapy, improvement of neuropsychiatric symptoms from all of the patients was observed. Over a mean follow-up of 30.8 weeks, all of the patients had marked improvement in the modified Rankin Scale. To date, no tumors were not observed in any patients. Conclusions: Anti-DPPX encephalitis mainly presents as neuropsychiatric symptoms. Cooperation of DPPX antibodes and CASPR2 antibodies might have contributed to the migration of myoclonus in the patient 4. Prompt immunotherapy often results in improvement.